THE INTERPLAY BETWEEN ACADEMIC MOTIVATION AND PROFESSIONAL SELF-DETERMINATION AMONG MIDDLE SCHOOL STUDENTS - Turdymuratova, Amangul Baimuratovna; Dzhapakova, Laura (SCIENCE and SOCIETY, 2026)
This article analyzes the theoretical foundations of student motivation and its role in career choice. The concept of motivation is described based on psychological perspectives from antiquity to the present day (Wentzel, Schunk, Maslow, etc.). The study examines the influence of internal and external factors on increasing the academic activity of middle school students, as well as modern methods for assessing motivation. The results highlight the strategic importance of motivation in the process of vocational guidance and the role of the educational environment in this process.
Keywords: motivation; career choice; academic activity; student; psychological theories; vocational guidance